PENGEMBANGAN DESAIN KURIKULUM MUATAN LOKAL LITERASI LINGKUNGAN DI SEKOLAH DASAR BERBASIS SUSTAINABLE DEVELOPMENT GOALS 2030 : Model Design Based Research di Lingkungan Objek Wisata Situ Ciburuy - Iku Firman Mauludin, - (2019)
The background of this study is that there is environmental damage in the Ciburuy lake, the main causal factors are irresponsible community behavior and lack of coordination between the village governmental, the community and educational institutions such as schools. Through the development of local curriculum design with environmental literation in primary school to prepare and enhance students' critical thinking early, on preservation and the noble values of local wisdom and integrate sustainable development goals (SDG's) 2030 as global insights. This study aims to find out the competencies, content, teaching strategies, and evaluation instruments of learning outcomes that are needed in support development of local curriculum design with environmental literation in primary school based on SDG's 2030 conducted around Ciburuy Lake and 3 nearby Primary Schools such as SDN 1 Ciburuy, SDN 2 Ciburuy and SDN Sadang, by applying a qualitative approach to ethnographic procedures in case studies of design based research (DBR), Non Probability sampling using instruments 1). environmental observation of Ciburuy lake, 2). interview to 3 primary school principals above, 3 community leaders and Ciburuy village head 3). open questionnaire to 18 teachers of all classes (grades 1- grade 6) from 3 primary schools above. Obtained results, for attitude competencies: 1). able to show behavior that is in accordance with the values and regulations; 2). Students are able to adopt a healthy lifestyle; 3). able to cooperate in maintaining environmental sustainability: 4). Students are able to be critical in maintaining environmental sustainability. for knowledge competencies: 1). able to explain the concept of environmental sustainability; 2). able to identify the values contained in history and fairy tales of Ciburuy lake; 3). able to explain the biodiversity of Situ Ciburuy; 4). able to classify types of waste; 5). able to explain the behavior of maintaining cleanliness and environmental sustainability: 6). able to explain the potential, benefits and role of lake Ciburuy. For skills competencies: 1). able to maintain several types of fish that live in Ciburuy Situ; 2). able to farming; 3). Skilled in arts and sports; 4). Students are able to make handicraft products of artistic and economic value. For material: 1). Concept of environmental sustainability; 2). knowledge of Ciburuy Lake; 3). Types and handling methods waste; 4). Biodiversity in Ciburuy lake; 5). Sundanese cultural skills. For expository strategies it is suitable for primary students in grades 1,2,3 and 4, while for strategies for inquiry can be applied to all classes. Evaluation instrument to assess knowledge: Matching, essay, MC, True-False, verbal. To assess the attitude: Interview, Likert and Thurstone Scale. To assess skill: Performance Rubrics, observation rubrics, product assessments, Portfolios, project assessments.